Myths America lives by : white supremacy and the stories that give us meaning - Hughes, Richard T. (Richard Thomas), 1943- (University of Illinois Press, 2018)
"In the first edition of Myths America Lives By, Hughes identified the five key myths that lie at the heart of the American experience-the myths of the Chosen Nation, of Nature's Nation, of the Christian Nation, of the Millennial Nation, and of the Innocent Nation. Drawing on a range of dissenting voices, Hughes shows that by canonizing these seemingly harmless myths of national identity as absolute truths, America risks undermining the sweepingly egalitarian promise of the Declaration of Independence. Hughes demonstrates that Americans must rethink these myths in the spirit of extraordinary humility if the United States is to fulfil its true promise as a nation. Hughes locates the roots of each myth in a different period of America's development, and from each of these periods he finds stirring critiques offered by marginalized commentators-especially African Americans and Native Americans-who question the predominant myth of their age. This is a dialog between the mainstream mythmakers and the many critics--including Martin Luther King Jr., Ida B. Wells, Frederick Douglass, Black Elk, Anna J. Cooper, and Booker T. Washington, Malcom X, Angela Davis, and W. E. B. DuBois-whose dissent, rather than being un-American, was often grounded in a patriotic belief in the "self-evident" equality of America's fundamental creed. The second edition of Myths America Lives By continues to investigate how the myth of white supremacy has intersected and continues to intersect with foundational American myths with an entirely new introduction and updates to each myth"--